Familiarizing with using herbal eutracts in Isfahan Province - I Golshadi; R Ansari; S Asgary; N Sarrafzadegan; M Boshtam (Institue of Medicinal Plants, ACECR, 2002)
In the past, herbs were considered as the primary and most available therapeutic source. Although therapeutic herbs have been limited to be consumed through chemical and synthetic drugs with all diversities, recently they are considered interesting for treatment of disease in the world elucidating the importance of public knowledge and attitude for their accurate usage with physician's advice (pharmacologist or herbal physician). As one of the aims of pharmocognosy is knowing and evaluating herbal drugs, it appreciates that more effort would be performed to introduce these natural riches to public, and generally determine the situation of herbal medicine for public and physicians, and elucidate their benefits for people. This study aimed to determine the level of public knowledge, attitude and practice regarding usage of herbal drugs and tries to promote public to consume these herbs, determining the existing lacks and suggesting practical strategies to improve the situation of herbal medicine. This descriptive qualitative study was performed on the adults aged twenty years up in Isfahan population through multistage sampling. Twenty clusters were selected randomly among 200 clusters in Isfahan population. From each clusters, 84 people aged 20 years up was randomly selected (42 men, 42 women). The total sample size was 1680. The tool for data collection was questionnaire completed through interviewing. This questionnaire included 23 questions (for evaluating knowledge, attitude and practice there were four questions each). The questions were categorized to three levels of credit including weak, moderate & good. The data was entered to a file in SPSS and statistically analyzed with Kruskal Wallis, Mann Withney & also obtained descriptive statistically (including frequency & standard deviation). In this study, 63% of men had a knowledge level of weak to moderate and 59% of women had the good knowledge. Also, 50% of total subjects in all age groups were in a good level for knowledge and less than 50% of them had the weak or moderate knowledge. Regarding attitude, both sexes were good and regarding practice both were weak. Generally, the knowledge, attitude and practice of women were better then men's (P=0.001). Also, there was no significant difference among different age groups as knowledge, attitude & practice regarding usage of herbal drugs (P>0.05). The results showed that women were better than men in all studied aspects probably due to more exposition of women to mass media and having more time for usage of these sources. Also, women have more time to discuss & interchange opinions but men interchange their thought mainly on economic aspects and eliminating problems & obstacles at work. Also the results showed that the practice was weaker than attitude & knowledge in both sexes that probably is due to the ignorance regarding preparation and usage of herbal drugs. It determines the necessity of education by four groups: mass media, intermediate education, high education, clinical- research education in scientific centers and universities.